Changes in socioeconomic determinants of health in a copper mine development area, northwestern Zambia. Issue 4 (December 2021) - Zabré, Hyacinthe R.; Knoblauch, Astrid M.; Diagbouga, Serge P.; Fink, Günther; Owuor, Milka; Nduna, Kennedy; Chisanga, Marcus; Musunka, Gertrude; Divall, Mark J.; Winkler, Mirko S.; Farnham, Andrea
Highlights: Predominantly positive changes in socioeconomic indicators have been observed in communities affected by a large-scale copper mine in Zambia. Mine-impacted communities showed generally better socioeconomic development as compared to non-impacted comparison communities. Collaboration and shared responsibilities between the private and the public sectors are necessary to prevent development of inequalities and inequities between communities and households. Health impact assessment (HIA) is a tool to monitor socioeconomic and other indicators and to evaluate the impacts of mining projects on local communities. Abstract: In 2011, an industrial copper mine was developed in northwestern Zambia. A health impact assessment was conducted to anticipate and address potential health impacts. To monitor these impacts, three community-based surveys were conducted in the area (2011, 2015 and 2019). We analysed these data to determine how household socioeconomic indicators – considered determinants of health – have changed in the area over time. In mine-impacted communities, between 2011 (pre-construction) and 2019, significant changes were observed for: (i) average household size (-0.6 members); (ii) proportion of mothers that have not completed primary school (+20.4%); (iii) ownership of economic assets (e.g. phones +29.3%; televisions +15.6%); (iv) access to safe drinking water (+27.4%); and (v) improved housing structures (e.g. finished roof +58.6%). When comparing changes between 2015 and 2019 in impacted communities to nearby comparison communities, there was (i) an increased proportion of mothers that had not completed primary school in comparison communities vs . no change in impacted communities; and (ii) increased ownership of economic assets in impacted vs. comparison communities in 2019. This study found generally positive changes in the socioeconomic development of impacted compared to comparison communities, with the most pronounced improvements in the early phases of mine development.